Parents' migration and children's subjective well-being and health: evidence from rural China - Murphy, R; Zhou, M; Tao, R (Wiley, 2015)
This study examines differences in children's subjective well‐being and health across the full range of family structures that have emerged in China's rural areas because of parental labour migration. It uses original cross‐sectional survey data collected in 2010 in Anhui and Jiangxi provinces from children aged 8–17 years, as well as from their teachers and guardians (n = 992). The results indicate no significant difference between ‘left‐behind’ children and other children for satisfaction with life events. However, the results do demonstrate that left‐behind children fare worse than children who live with both parents for behaviour at school, confidence in the realisation of future goals, loneliness, and health. The results further reveal that who migrates matters for children's well‐being. Specifically, children with two migrant parents fare worse than children with only one migrant parent for several dimensions of well‐being including behaviour and loneliness. Meanwhile, the children of lone migrant mothers fare worse than all other children for selected measures, most notably health. Following other scholars, our analyses underscore the sensitivity of the results to the dimension of child well‐being measured and to who provides the evaluation.